A Survey of Product Recognition in Shelf Images - Melek, Ceren Gulra; Sonmez, Elena Battini; Albayrak, Songul (IEEE, 2017)
Nowadays, merchandising is one of the significant method which allows to increase the sales. Therefore, activities such as monitoring the number of products on the shelves, completing the missing products and matching the planogram continuously have become important. An autonomous system is needed to automate operations such as product or brand recognition, stock tracking and planogram matching. In the literature, it is seen that many studies have been carried out in order to address this issue. This survey classifies and compares all existing works with the aim to guide researchers working on merchandising.
Keywords: product recognition; planogram matching; brand recognition; stock tracking; Computer Science